X-Ray Free Minimally Invasive Surgery for Urolithiasis in Pregnancy - Basiri, Abbas; Nouralizadeh, Akbar; Kashi, Amir Hossein; Radfar, Mohammad Hadi; Nasiri, Mahmood Reza; Zeinali, Mahdi; Sarhangnejad, Reza; Hosseini-Sharifi, Seyed Hossein (Urology Journal, 2016)
Purpose: Our goal was to present our experience with ultrasound guided supine or prone percutaneous nephrolithotomy in three pregnant women under spinal anesthesia. Materials and Methods: Three pregnant women in the 16th, 20th and 28th weeks of pregnancy presented with symptomatic large renal stone in the first patient and multiple renal stones in the second and third patients which were unresponsive to conventional medical therapy. They requested a definitive stone treatment. The operations were done in November 2012, June 2014 and February 2015. Data was gathered prospectively. All steps of gaining access to the pyelocalyceal system including needle insertion, tract dilation, and Amplatz sheath placement were performed under ultrasonography guidance. Tract was dilated with a single shot technique. The first two procedures were performed in supine position and the third procedure was performed in lateral flank position. Results: Two patients were stone-free postoperatively and one patient had only an asymptomatic 4 mm residual stone. They were discharged on the 2nd postoperative day and had an uneventful postoperative course. No fever, bleeding or renal colic was noticed during postoperative hospitalization. All patients delivered their fetuses at term without any abnormality reported by the examining pediatric specialist after their birth. Conclusion: Ultrasonography can be used as an imaging modality guiding all steps of obtaining percutaneous access in pregnant women. Supine or flank ultrasound guided percutaneous nephrolithotomy can be offered to pregnant women in whom conservative measures fail to the patients' wellbeing.